Development of finite different lattice boltzmann scheme for the computation of natural convection heat transfer - Osman, Shahrul Azmir (2009)
This thesis presents a numerical study of flow behavior from a heated concentric annulus cylinder at various Rayleigh number Ra, Prandtl number Pr and aspect ratio of the outer and inner cylinders. The finite different lattice Boltzmann method (FDLBM) numerical scheme is developed to improve the computational efficiency and numerical stability of the conventional method. The proposed FDLBM applied UTOPIA approach (third order accuracy in space) to study the temperature distribution and the vortex formation in the annulus. D2Q9 velocity model was coupled with D2Q4 velocity model to represent the density and internal energy distribution function respectively. The comparison of the flow pattern and temperature distribution for every case via streamline, vortices and temperature distribution contour with published paper in literature were carried out for the validation purposes. Current investigation concluded that the UTOPIA FDLBM is an efficient approach for the current problem in hand and good agreement with the benchmark solution